The Effect of Audiovisual Media on Students' Creative Thinking Ability in Class V Science Subject - Hercahyo Adhon Pribadi; Harlinda Syofyan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find out whether audio-visual media had an effect on students' creative thinking abilities at SDN Kampung Bambu 1 in science class V. This research was an experimental quantitative study. The sampling technique used was nonprobability sampling with a saturated sample model with a total of 70 students. The research instrument consisted of 16 essay questions and a questionnaire consisting of 20 statement items. The results of this study indicate that the use of audiovisual media affects students' creative thinking abilities in science subjects. The t-test shows that the use of audio-visual media has a significant effect of 0.001 <0.05 on the creative thinking of fifth grade students at SDN Kampung Bambu 1 in science subjects